2009
DOI: 10.3795/ksme-b.2009.33.7.520
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Plate Heat Exchanger with Chevron Angle Variations

Abstract: The objectives of this paper are to measure the heat transfer and pressure drop of the plate heat exchangers for absorption system applications. Three types of plate heat exchangers with different chevron angles are tested in the present experiment. Heat transfer and pressure drop performance of plate heat exchangers are measured in various operating conditions, and compared each other. The results show that the heat transfer rate of high theta (120°) and mixed theta plate heat exchanger increases about 118% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…However, to the best of our knowledge, no extant study has investigated the difference, and it is therefore considered useful to examine the difference through this study. When the existing correlations based on LiBr/LiBr were compared with the LiBr/water results of this study, Kwon et al [19] exhibited large errors of less than 60%, Song et al [21] less than 30%, and Kim et al [18] less than 50%. While Kim et al [18] and Song et al [21] showed tendencies similar to that of this study, despite the large errors in Nu, Kwon et al [19] exhibited a significantly different increasing tendency for Nu compared to the results of this study.…”
Section: Development Of Nu Correlationmentioning
confidence: 70%
See 3 more Smart Citations
“…However, to the best of our knowledge, no extant study has investigated the difference, and it is therefore considered useful to examine the difference through this study. When the existing correlations based on LiBr/LiBr were compared with the LiBr/water results of this study, Kwon et al [19] exhibited large errors of less than 60%, Song et al [21] less than 30%, and Kim et al [18] less than 50%. While Kim et al [18] and Song et al [21] showed tendencies similar to that of this study, despite the large errors in Nu, Kwon et al [19] exhibited a significantly different increasing tendency for Nu compared to the results of this study.…”
Section: Development Of Nu Correlationmentioning
confidence: 70%
“…When the existing correlations based on LiBr/LiBr were compared with the LiBr/water results of this study, Kwon et al [19] exhibited large errors of less than 60%, Song et al [21] less than 30%, and Kim et al [18] less than 50%. While Kim et al [18] and Song et al [21] showed tendencies similar to that of this study, despite the large errors in Nu, Kwon et al [19] exhibited a significantly different increasing tendency for Nu compared to the results of this study. These differences occurred because experiments were performed at higher inlet temperatures in the previous studies compared to this study, and the previous studies had lower Nu results at similar Re levels as they had lower Prandtl numbers (Pr).…”
Section: Development Of Nu Correlationmentioning
confidence: 70%
See 2 more Smart Citations
“…They carried out both the numerical analysis and the experiments and found that the elliptic embossing type gave better heat transfer performance than the chevron type plate and a lower pressure drop than the other plates under the same geometric and thermal conditions. Kwon et al 7 carried out experiments for the high temperature solution heat exchanger. They evaluated the heat transfer and pressure drop characteristics by changing the chevron angle and derived a Nusselt number and friction factor correlation.…”
Section: Introductionmentioning
confidence: 99%